In Site Generation of Well‐Dispersed Ag3PO4 NPs on Protein‐Inorganic Hybrid Nanoflowers with Enhanced Catalytic Performance. Issue 10 (9th March 2022) - Ji, Chunxiao; Zheng, Jing; Jin, Yuqin; Yin, Xue‐bo; Han, Suping; Zhang, Min
Abstract: Developing environmental‐friendly and high‐performance catalysts hold excellent prospects for pollution control. Herein, a novel nanocatalyst is successfully prepared through a facile in‐situ deposition method upon bridging copper phosphate and the protein, which allowing uniform Ag3 PO4 NPs to be immobilized on both inner and outer hierarchical nanoflowers. Results show that the fabricated hierarchical flower‐like architecture of Cu3 (PO4 )2 @BSA@Ag3 PO4 composite demonstrated superior catalytic performance for the hydrogenation of 4‐nitrophenol. Moreover, the hybrid nanoflowers hold a high conversion rate (around 95.4 %) and recycling stability over five reaction cycles. Therefore, such a convenient, economical and green approach to synthesize recyclable nanoflowers possesses broad application potential for the treatment of agricultural and industrial wastewater. Abstract : Herein, a novel nanocatalyst is successfully prepared through a facile in‐situ deposition method upon bridging copper phosphate and the protein, which allowing uniform Ag3 PO4 NPs to be immobilized on both inner and outer hierarchical nanoflowers.The catalytic activities of the Cu3 (PO4 )2 @BSA@Ag3 PO4 nanoflower for the reduction of 4‐nitrophenol (4‐NP) were tracked, and the nanoflower exhibited high catalytic activity, which might be attributed to the high surface areas of Ag3 PO4 and synergistic effect on the delivery of electrons between the Cu3 (PO4 )2 @BSA and Ag3 PO4 .